Preparation and Characterization of Nanofibres of 2ZnO·3B2O3·5H2O Ceramic Composite Using Sol-Gel Processing - Sevim, Fatih; Kara, Adem; Aksakal, Oguz; Demir, Fatih; Eroglu, Hayrettin (Asian Journal of Chemistry, 2015)
2ZnO·3B2O3·nH2O (zinc borate) having the industrially important composite and used as flame retardant, anti-smoke and semiconductor in the electronic circuits was examined with different crystal structures. In this study, nanofibers of PVA/zinc nitrate/boric acid composite were prepared by using sol-gel processing and electrospinning technique. By high temperature calcinations of the above precursor fibers, nanofibers of 2ZnO·3B2O3·5H2O composite with diameters of 110 nm could be successfully obtained. The products have been characterized by X-ray powder diffraction, thermogravimetry and differential thermal analysis, scanning electron microscopy and Fourier transform-infrared spectroscopy. The effects of experimental conditions on the products were investigated.